Socialization of Antibiotic Resistance and The Correct Use of Antibiotics in The Village of Sindangpalay - Isye Martiani; Noviyanti Noviyanti; Ananda Gelar Pamungkas; Fadel Muhammad; Ilham Aliyap; Sandy Firmansyah (Fakultas Kewirausahaan Universitas Garut, 2022)
Abstract Antibiotics are a class of compounds, both natural and synthetic, which have the effect of killing or inhibiting bacterial growth, thus dealing with bacteria is very careful if you do not know that their use will lead to antibiotic resistance. Antibiotic resistance is defined as the resistance of bacteria to antibacterials so that antibacterials have no effect at the usual doses used. This service aims to educate the general public to know how to use antibiotics properly and correctly so as not to cause resistance. Before the presentation of the material was carried out, we asked the audience first, it appeared that the audience did not know about the material. The method we use is by delivering the material to the audience, then a question and answer session and there is a session where we ask questions and the audience answers so that it can be seen that the audience understands what we are conveying. The result of this service is that the audience understands the material that has been conveyed by them and can answer the questions we give. Abstrak Antibiotik adalah golongan senyawa, baik alami maupun sintetik, yang memiliki efek membunuh atau menghambat pertumbuhan bakteri, dengan demikian berhubungan dengan bakteri sangatlah berhati-hati jika tidak tahu penggunaanya akan menimbulkan resistensi antibiotic. Resistensi antibiotik didefinisikan sebagai ketahanan bakteri terhadap antibakteri sehingga antibakteri tidak berefek pada dosis lazim yang digunakan. Pengabdian ini bertujuan untuk mengedukasi masyarakat awam agar mengetahui cara penggunaan antibiotik yang baik dan benar sehingga tidak menyebabkan resistensi. Sebelum pemaparan materi dilakukan kami bertanya terlebih dahulu kepada audien, terlihat bahwa audien tidak mengetahui tentang materi tersebut. Metode yang kami gunakan dengan menyampaikan materi ke audien selanjutnya sesi tanya jawab dan ada sesi dimana kami yang bertanya kemudian audien menjawab sehingga dapat dilihat bahwa audien mengerti dengan apa yang kami sampaikan. Hasil dari pengabdian ini adalah audien memahami materi yang telah disampaikan dengan mereka bisa menjawab pertanyaan yang kami berikan.